2010
DOI: 10.1007/s10787-009-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of the nitric oxide donor isosorbide-5-mononitrate alone and in combination with the natural hepatoprotectant, silymarin, on carbon tetrachloride-induced hepatic injury in rats

Abstract: The aim of this study was to investigate the effect of the nitric oxide donor isosorbide-5-mononitrate (5-ISMN) alone or in combination with the natural hepatoprotectant with anti-oxidant activity silymarin on the carbon tetrachloride (CCl(4))-induced hepatic injury in rats. 5-ISMN (1.8, 3.6 or 7.2 mg/kg), silymarin (25 mg/kg) or 5-ISMN (1.8, 3.6 or 7.2 mg/kg) combined with silymarin was given once daily orally simultaneously with CCl(4) and for 15 days thereafter. Liver damage was assessed by determining seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Results from animal models applying CCl 4 as well as other hepatotoxic agents, e.g. paracetamol, show a significant change in hepatic acute phase enzymes and pro-fibrotic markers due to silymarin application (Table 2) [67,68]. In a further experiment in rats, using CCl 4 as the offending agent, a dose of 50 mg/ kg of silymarin was found to be more effective than 200 mg/kg in reducing oxidative stress, lysis of hepatocytes, activation of Kupffer cells, and the expression of alpha smooth muscle actin (α-SMA) and transforming growth factor beta 1 (TGF-β1) [54].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Results from animal models applying CCl 4 as well as other hepatotoxic agents, e.g. paracetamol, show a significant change in hepatic acute phase enzymes and pro-fibrotic markers due to silymarin application (Table 2) [67,68]. In a further experiment in rats, using CCl 4 as the offending agent, a dose of 50 mg/ kg of silymarin was found to be more effective than 200 mg/kg in reducing oxidative stress, lysis of hepatocytes, activation of Kupffer cells, and the expression of alpha smooth muscle actin (α-SMA) and transforming growth factor beta 1 (TGF-β1) [54].…”
Section: Animal Modelsmentioning
confidence: 99%
“…In different oncological diseases, such as prostate cancer, cervical cancer, hepatocellular carcinoma (HCC), bladder cancer and lung cancer, silymarin reduces cell vitality and runaway cell replication [ 48 , 49 , 50 , 51 , 52 ]. Because of its detoxifying power, its hydrosoluble endovenous formulation, it is used as an anti-hepatotoxic drug in poisonings due to acetaminophen, arsenic, carbon tetrachloride, butyrophenones, phenothiazines and Amanita phalloides toxins [ 53 , 54 , 55 , 56 ]. In hypercholesterolemia, silymarin inhibits 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, reducing cholesterol synthesis [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salam et al reported that a dose of 7,2 mg · kg −1 ISMN applied by gastric gavage protected rats against hepatic injury and hepatocellular necrosis induced by carbon tetrachloride (see Additional file 1: Table S2) [31]. Therefore, we assumed that ISMN could also reduce the development of large confluent hepatocellular necrosis caused by outflow obstruction after extended liver resections and RHMV ligation [4].…”
Section: Discussionmentioning
confidence: 99%